Role of chondroitin sulphate tethered silk scaffold in cartilaginous disc tissue regeneration. (8th April 2016) - Bhattacharjee, Maumita; Chawla, Shikha; Chameettachal, Shibu; Murab, Sumit; Bhavesh, Neel Sarovar; Ghosh, Sourabh
Abstract: Strategies for tissue engineering focus on scaffolds with tunable structure and morphology as well as optimum surface chemistry to simulate the anatomy and functionality of the target tissue. Silk fibroin has demonstrated its potential in supporting cartilaginous tissue formation both in vitro and in vivo . In this study, we investigate the role of controlled lamellar organization and chemical composition of biofunctionalized silk scaffolds in replicating the structural properties of the annulus region of an intervertebral disc using articular chondrocytes. Covalent attachment of chondroitin sulfate (CS) to silk is characterized. CS-conjugated silk constructs demonstrate enhanced cellular metabolic activity and chondrogenic redifferentiation potential with significantly improved mechanical properties over silk-only constructs. A matrix-assisted laser desorption ionization-time of flight analysis and protein–protein interaction studies help to generate insights into how CS conjugation can facilitate the production of disc associated matrix proteins, compared to a silk-only based construct. An in-depth understanding of the interplay between such extra cellular matrix associated proteins should help in designing more rational scaffolds for cartilaginous disc regeneration needs.